Food Security Governance: Bibliometric Mapping and Comparative Policy Lessons for Indonesia - Zulkifli Hasan; Hadi Daryanto (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Food security governance remains critical as global challenges like climate change and distribution inefficiencies threaten equitable access to food, particularly in archipelagic nations like Indonesia. This study aims to analyze global trends in food security policy and derive actionable governance lessons for Indonesia through a dual approach. It employs bibliometric analysis of 128 journal articles published between 2010 and 2024, using Scopus data processed with RStudio’s Bibliometric tool, alongside a comparative review of food security strategies in India, Brazil, China, and Ethiopia. Findings reveal a shift in global research toward sustainability, resilience, and governance, with key journals and keywords emphasizing interdisciplinary approaches. The comparative analysis highlights India’s digital reforms for transparent distribution, Brazil’s agroecological initiatives for smallholder empowerment, China’s technology-driven self-sufficiency, and Ethiopia’s community-based resilience programs. These strategies offer transferable lessons for addressing Indonesia’s logistical and climate-related challenges. The study concludes that Indonesia can enhance its food security by integrating digital governance, sustainable farming practices, technological investments, and community-driven resilience programs.